The wandering uterus : politics and the reproductive rights of women - Meyer, Cheryl L., 1959- (Book collections on Project MUSE., 1997)
From the FDA review of RU-486 to the recent growth of fertility clinics to the rights of lesbian parents, women's reproductive lives are aggressively regulated by law and medicine. While a great deal has been written on such issues as abortion and postpartum depression, no single volume has offered a broad discussion of the interface between the legal, medical, and political aspects of women's reproduction in a manner accessible and informative to non-specialists. The Wandering Uterus fills that gap. Taking her title from an ancient Greek belief that women's health problems were caused by a wandering uterus that needed to be confined and controlled, Meyer exposes the way in which myths and prejudice about female sexuality continue to influence the practice of law and medicine today. This book offers new insights and provides a wealth of up-to- date information on a subject that changes every day. The text is divided into three main parts: political issues of pre- conception, the politics of pregnancy, and the politics of motherhood. Throughout, Meyer argues passionately that while technology and medicine must progress, they should not be allowed to do so at women's expense.